2021
DOI: 10.1101/2021.06.07.447386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A particle size threshold governs diffusion and segregation of PAR-3 during cell polarization

Abstract: Regulation of subcellular components' localization and motion is a critical theme in cell biology. Cells use the actomyosin cortex to regulate protein distribution on the plasma membrane, but the interplay between membrane binding, cortical movements and protein distribution remains poorly understood. In a polarizing one-cell stage Caenorhabditis elegans embryo, actomyosin flows transport PAR protein complexes into an anterior cortical domain to establish the anterior-posterior axis of the animal. Oligomerizat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…Alternatively, engineered clusters could be used to study transport properties. Recent experimental work by Chang and Dickinson (2021) took this approach. Their new data suggests that clusters of size 3 or larger indeed exhibit directed transport, that the transport of larger clusters is more ballistic (as opposed to diffusive), and that the cluster diffusion constant decreases with clus ter size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, engineered clusters could be used to study transport properties. Recent experimental work by Chang and Dickinson (2021) took this approach. Their new data suggests that clusters of size 3 or larger indeed exhibit directed transport, that the transport of larger clusters is more ballistic (as opposed to diffusive), and that the cluster diffusion constant decreases with clus ter size.…”
Section: Discussionmentioning
confidence: 99%
“…These experimental investigations also revealed that the cortical residence times of clusters and their persistence of motion both increase with cluster size, raising the more specific question of how larger clusters are more effectively transported. Chang and Dickinson (2021) engineered PAR3 clusters of various sizes and found that clusters of size three (i.e., consisting of three PAR3 monomers) or larger are the minimum size required transport by flow to obtain polarity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation